2016
DOI: 10.1007/s40204-016-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of eri and tasar silk fibroin scaffolds for biomedical applications

Abstract: The cultivated silk, mulberry, is being used as biomaterial in different forms. Eri, tasar and muga are some of the known wild silk varieties. The studies on biomedical applications of electrospun mats produced from these wild silks are limited though few studies on eri silk are available. In this work, comparison was made between eri and tasar silk fibroin scaffolds for biomedical application. The scaffolds were produced from eri silk fibroin (ESF) and tasar silk fibroin (TSF) by electrospinning method and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Three peaks located at 2 values of 14.36 , 16.99 and 21.12 in both patterns corresponded to the crystalline diffraction of SS-finished silk fibers. 44,45 After in situ synthesis of CuNPs, three further peaks appeared at 2 values of 43.75 , 50.89 and 74.65 , which agreed well with the 111, 200 and 220 diffractions of the facecentered cubic structure of metallic Cu. 26 This confirmed that CuNPs had been successfully loaded onto the SS-finished silk fabrics.…”
Section: Characterization Of Ss-cunps and Functionalized Silk Fabricssupporting
confidence: 69%
“…Three peaks located at 2 values of 14.36 , 16.99 and 21.12 in both patterns corresponded to the crystalline diffraction of SS-finished silk fibers. 44,45 After in situ synthesis of CuNPs, three further peaks appeared at 2 values of 43.75 , 50.89 and 74.65 , which agreed well with the 111, 200 and 220 diffractions of the facecentered cubic structure of metallic Cu. 26 This confirmed that CuNPs had been successfully loaded onto the SS-finished silk fabrics.…”
Section: Characterization Of Ss-cunps and Functionalized Silk Fabricssupporting
confidence: 69%
“…Four peaks located at 2θ values of 14.06 • , 17.22 • , 20.75 • , and 28.04 • in both patterns corresponded to the crystalline diffraction of silk fibers [33,34]. After in situ synthesis of AgNPs, three more peaks appeared at 2θ values of 38.41 • , 46.08 • , and 64.45 • , which agreed well with the (111), (200), and (220) diffractions of the face centered cubic (fcc) structure of metallic Ag [35].…”
Section: Characterization Of Ss-agnp and Functionalized Silk Fabricsmentioning
confidence: 89%
“…Similar results have been reported by Andiappan et al showing one weight loss at 100°C and a second at 370°C for tasar silk fibroin scaffolds. 38 Also, for blend films, as observed in Fig. 5, there is a visible shift in the weight loss curve towards lower temperature due to the blending of silk fibroin with gelatin.…”
Section: Resultsmentioning
confidence: 69%
“…Similar results have been reported by Andiappan et al . showing one weight loss at 100 °C and a second at 370 °C for tasar silk fibroin scaffolds 38 …”
Section: Resultsmentioning
confidence: 99%